Barriers and facilitators of transition of adolescents living with HIV into adult care in under-resourced settings of Southern Ethiopia: a qualitative study - Mulugeta Shegaze Shimbre; Belay Boda Bodicha; Abakundana Nsenga Ariston Gabriel; Lubna Ghazal; Kedi Jiao; Wei Ma (BMC, 2024)
Abstract Background Adolescence is commonly perceived as a distinct and typically healthy stage of life. However, in regions with a high prevalence of HIV, like Ethiopia, numerous adolescents are contracting the virus. Upon testing and diagnosis, they encounter care-related issues, particularly barriers and facilitators of the healthcare transition from adolescent to adult clinics. Hence, the study aimed to investigate the barriers and facilitators influencing the transition of adolescents living with HIV (ALWHs) in the resource-limited settings of Southern Ethiopia. Methods The research employed a phenomenological study design with a qualitative methodology. Purposive sampling was used to gather data through in-depth interviews (IDIs) and focus group discussions (FDGs) involving ALWHs and their parents. The data analysis followed Van Manen's principles. Results Following Van Manen's guidelines, the data analysis revealed a conceptual framework with two major themes: "Barriers" and "Facilitators". The theme barrier was derived from three sub-themes including behavioral barriers, social barriers, and system barriers in the transition. The theme facilitator was derived from four sub-themes including self-acceptance as an adult, a desire to experience new things, a supportive family, and friendly healthcare services. The study identified three levels of factors influencing the transition into adult clinics: individual, family/peer, and healthcare-related factors. The barriers to transition included lack of knowledge, being in a romantic relationship, psychosocial struggles, perceiving us as immature, stigma, negative peer pressure, lack of timely disclosure, absence of transition guidelines, disrespectful treatment, and absence of separate clinics. On the other hand, facilitators such as self-acceptance as an adult, desire for new experiences, family support, informed support and promising outcomes, flexible appointment scheduling, and psycho-social support groups were found to improve the transition process and enhance the overall well-being of adolescents living with HIV. Conclusion The study highlights the complex transition process for ALWHs into adult healthcare. Barriers such as lack of knowledge, stigma, and disrespectful treatment pose challenges during this critical period. Conversely, facilitators like self-acceptance, family support, and youth-friendly healthcare services can enhance the transition experience and well-being of ALWHs. Collaborative efforts among ALWHs, families, and healthcare providers are crucial for successful transitions and improved health outcomes. Separated clinics catering to the unique needs of ALWHs are recommended to address privacy concerns.